A COMPLETE AND UPDATED REVIEW ON VARIOUS TYPES OF DRUG DELIVERY SYSTEMS - GARG, RAJEEV; KAUR, SHARANPREET; RITIKA; KHATOON, SHEHNAZ; NAINA; VERMA, HITESH (International Journal of Applied Pharmaceutics, 2020)
The World of medicine has gained considerable interest in the research area all over the World. Scientists constantly work on the three parameters ‘Quality, Safety, Efficacy’ of a pharmaceutical ingredient. Refine these parameters; they are continually developing different dosage forms. These unique types of dosage forms help to provide improved bioavailability and efficacy of a pharmaceutical ingredient. The role of dosage form is to improve the availability of the medicine to treat the symptoms and disease. This article focus on the different types of dosage forms, their advantages and some important facts related to that dosage forms.